Heterotopic pregnancy: case report of a successful first trimester metacyesis management and a viable third trimester outcome - Singh, Arvind Kumar; Khan, Shazia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Heterotopic pregnancies are rare combined intra and extrauterine pregnancies, the incidence of which has shown an increase over the past decade with the rising trend in assisted reproductive technologies (0.75-1.5%). Authors report a case of a 29 year old primigravida, a post IVF conception who presented at 6 weeks POG with a ruptured tubal and a viable intrauterine pregnancy. She underwent an emergency laparoscopic right salpingectomy and continued with her intrauterine pregnancy successfully till term. The article emphasizes the need of scanning the adnexa carefully in early pregnancy to diagnose and manage heterotopic pregnancy as early as possible to prevent catastrophic haemorrhage and maternal morbidity and mortality later.